Humanization of Yeasts for Glycan-Type End-Products - Li, Xingjuan; Shen, Jianlie; Chen, Xingqiang; Chen, Lei; Wan, Shulin; Qiu, Xingtao; Chen, Ke; Chen, Chunmiao; Tan, Haidong (Frontiers in Microbiology, 2022)
Yeasts are often considered microorganisms for producing human therapeutic glycosylated end-products at an industrial scale. However, the products with non-humanized glycans limited their usage. Therefore, various methods to develop humanized glycosylated end-products have been widely reported in yeasts. To make full use of these methods, it is necessary to summarize the present research to find effective approaches to producing humanized products. The present research focuses on yeast species selection, glycosyltransferase deletion, expression of endoglycosidase, and expression of proteins with galactosylated and or sialylated glycans. Nevertheless, the yeasts will have growth defects with low bioactivity when the key enzymes are deleted. It is necessary to express the corresponding repairing protein. Compared with N-glycosylation, the function of yeast protein O-glycosylation is not well-understood. Yeast proteins have a wide variety of O-glycans in different species, and it is difficult to predict glycosylation sites, which limits the humanization of O-glycosylated yeast proteins. The future challenges include the following points: there are still many important potential yeasts that have never been tried to produce glycosylated therapeutic products. Their glycosylation pathway and related mechanisms for producing humanized glycosylated proteins have rarely been reported. On the other hand, the amounts of key enzymes on glycan pathways in human beings are significantly more than those in yeasts. Therefore, there is still a challenge to produce a large body of humanized therapeutic end-products in suitable yeast species, especially the protein with complex glycans. CRISPR-Cas9 system may provide a potential approach to address the important issue.